Rare mucinous cystadenoma of minor salivary glands: Clinicopathologic analysis of 2 cases and review of literature - Oliveira, Denise Hélen Imaculada Pereira de; Freitas, Valéria Souza; Pacheco, Domingos Flávio Saldanha; Santos, Pedro Paulo de Andrade; Queiroz, Lélia Maria Guedes; Souza, Lélia Batista de (Journal of Oral Diagnosis, 2017)
Cystadenoma is a rare benign tumor of the salivary glands exhibiting clinical findings very similar to mucocele and, microscopically it may be confused with other lesions such as salivary duct cyst and cheilitis glandularis. It may be classified into two variants: papillary and mucinous, papillary variety being more common than mucinous with very few cases reported in literature. The aim of this work was reporting two cases of oral mucinous cystadenoma, and reviewing the literature regarding clinicopathologic aspects, differential diagnosis and therapeutic management specific to these tumors.